2019
DOI: 10.1021/acsami.9b11547
|View full text |Cite
|
Sign up to set email alerts
|

MxOy–ZrO2 (M = Zn, Co, Cu) Solid Solutions Derived from Schiff Base-Bridged UiO-66 Composites as High-Performance Catalysts for CO2 Hydrogenation

Abstract: Metal–organic frameworks have been exploited as excellent solid precursors and templates for the preparation integrated nanocatalysts with multicomponent and hierarchical structures. Herein, a novel synthetic protocol has been developed to fabricate versatile Zr-based solid solutions (such as ZnO–ZrO2, Co3O4–ZrO2, and CuO–ZrO2) via pyrolysis of Schiff base-modified UiO-66 octahedrons (size <100 nm), which were then utilized as efficient catalysts for CO2 hydrogenation. The Schiff base serves as an effective br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 63 publications
1
54
0
Order By: Relevance
“…When ZZO-4SZ5 is exposed to CO 2 + H 2 , the species of HCOO* (1584 cm −1 ) and slight CO 3 * (1694 and 1525 cm −1 ) are detected ( fig. S7A) (31)(32)(33)(34). When the catalyst is exposed to C 7 H 8 + CO 2 + H 2 , no any peak of CO 3 * is observed (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…When ZZO-4SZ5 is exposed to CO 2 + H 2 , the species of HCOO* (1584 cm −1 ) and slight CO 3 * (1694 and 1525 cm −1 ) are detected ( fig. S7A) (31)(32)(33)(34). When the catalyst is exposed to C 7 H 8 + CO 2 + H 2 , no any peak of CO 3 * is observed (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…21 ZrO 2 has been investigated as a support material in many binary and ternary systems for CO/CO 2 hydrogenation to methanol. [23][24][25][26][27][28][29] IR and TPD studies over pristine zirconia conducted by Pokrovski et al 30 showed that CO and CO 2 are mainly adsorbed as HCO − , CO 3 2− and HCO 3…”
Section: Introductionmentioning
confidence: 99%
“…These findings highlight that operation at high temperature thermodynamically favors side reactions, such as RWGS. 16 In another recent contribution, Li et al 29 used a metalorganic approach to prepare the catalysts by means of a Schiff base, yielding a Zn-doped ZrO 2 solid solution (with a 1 : 1 ratio). This catalyst showed a methanol selectivity of 70% with 5.7% CO 2 conversion at 320°C, V(CO 2 )/V(H 2 )/V(N 2 ) = 24/ 72/4% and GHSV = 18 000 mL g −1 h −1 .…”
Section: Introductionmentioning
confidence: 99%
“…7(B), observable peaks at 3600-3800 cm À1 are attributed to overtones of the gaseous CO 2 species for spent PdO@LaCoO 3 [35]. The intense bands at 2360-2450 cm À1 can be ascribed to stretching vibrations of the adsorbed gaseous CO 2 [50]. Meanwhile, the chemisorption of CO 2 results in the formation of peaks located at 1474, 1512, 1541, 1560 and 1627 cm À1 , which are assigned to the formation of carbonate and bicarbonate species, respectively [50].…”
Section: Co 2 -Tpd and In-situ Driftsmentioning
confidence: 97%